Milk and resistance exercise intervention to improve muscle function in community-dwelling older adults at risk of sarcopenia (MIlkMAN): protocol for a pilot study. Issue 10 (8th October 2019) - Granic, Antoneta; Hurst, Christopher; Dismore, Lorelle; Davies, Karen; Stevenson, Emma; Sayer, Avan A; Aspray, Terry
Abstract : Introduction: Sarcopenia is a progressive muscle disorder characterised by decline in skeletal muscle mass, strength and function leading to adverse health outcomes, including falls, frailty, poor quality of life and death. It occurs more commonly in older people and can be accelerated by poor diet and low physical activity. Intervention studies incorporating higher dietary protein intakes or protein supplementation combined with resistance exercise (RE) have been shown to limit muscle function decline. However, less is known about the role of whole foods in reducing the risk of sarcopenia. Milk is a source of high-quality nutrients, which may be beneficial for skeletal muscle. This pilot study examines the feasibility and acceptability of milk consumption with RE to improve muscle function in community-dwelling older adults at risk of sarcopenia. Methods and analysis: 30 older adults aged ≥65 years will be randomly allocated to three groups: 'whole milk+RE', 'skimmed milk+RE' or 'control drink+RE'. Assessments will take place in participants' homes, including screening (milk allergies, grip strength, walking speed), baseline and postintervention health and function. All participants will undertake a structured RE intervention twice a week for 6 weeks at a local gym, followed by the consumption of 500 mL of whole or skimmed milk (each ~20 g of protein) or an isocaloric control drink and another 500 mL at home. Participants' views about the study will be assessed using standardised open-ended questions. The primary outcomes include feasibility and acceptability of the intervention with recruitment, retention and intervention response rates. Analyses will include descriptive statistics, exploration of qualitative themes and intervention fidelity. Ethics and dissemination: Outputs include pilot data to support funding applications; public involvement events; presentation at conferences and peer-reviewed publication. Trial registration number: ISRCTN13398279 ; Pre-results.